Harvest data for 6 cowpeas and 6 maize farms in sandy soils in Makueni County, Kenya - Nyawira, Sylvia Sarah (2021)
The data shows the harvested yield in 6 maize farms and 6 cowpeas farms in Mtito Andei- Makueni County. The data was collected in 3 plots in each farm to compare crop productivity in sandy soils plots installed with the sub-surface water retaining technology (SWRT) against plots without this technology. 2 of the plots are installed with SWRT (plot 1 and 2) while the third plot is treated as the control plot. All the plots received equal amounts of manure and fertilizer during planting. The maize plots were also top-dressed.